2014
DOI: 10.1159/000360421
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity and Dysmorphology in Arabs

Abstract: Incidence rates of congenital disorders among the 350 million inhabitants of Arab countries could be influenced via the people's demographic and cultural characteristics. Arabs usually marry at a young age and have large families. They share certain core cultural values and beliefs, with the family accepted as the central structure of society. Consanguineous marriage is favored and respected in most if not all Arab communities, and intrafamilial unions currently account for 20-50% of all marriages. First-cousi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 116 publications
(112 reference statements)
0
37
1
Order By: Relevance
“…Therefore it is possible that consanguinity and genetic influence may be more potent than the environmental influence of sun exposure. Consanguinity is a common factor in the Muslim world . A number of population surveys have indicated that Israeli Arabs have a high rate of consanguinity ranging from 42% to 45% with 28% being first cousin marriages .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is possible that consanguinity and genetic influence may be more potent than the environmental influence of sun exposure. Consanguinity is a common factor in the Muslim world . A number of population surveys have indicated that Israeli Arabs have a high rate of consanguinity ranging from 42% to 45% with 28% being first cousin marriages .…”
Section: Discussionmentioning
confidence: 99%
“…Indicated groups include Ashkenazi Jews and Israeli Arabs. 2,3 Severe factor XI deficiency, also known as hemophilia C, is reported to have prevalence of 1:450 within the Ashkenazi Jewish community as compared with a 1:10 6 worldwide. 4 More modest factor XI deficiency, some of which may be autosomal dominant, has been estimated to be more common at 1 in 10 000 to 50 000.…”
Section: Introductionmentioning
confidence: 99%
“…1 In Arab countries, consanguinity accounts for 20% to 50% of all marriages, with higher rates in Egypt, Jordan, Kuwait, Palestine, Saudi Arabia, and Sudan. 2 In contrast, Latin America exhibits an intermediary situation, 1 with rates between 1% and 2% in Brazil, Colombia, Ecuador, Uruguay, and Venezuela. 3 In Brazil, changes in sociodemographic characteristics shrank the rates of consanguineous marriages from 4.8% 4 to 1.87% 3 in less than a half-century, but consanguinity remains high in some regions.…”
Section: Introductionmentioning
confidence: 99%